Improving Fine Motor Skills through the Finger Painting Method for Children with Mild Intellectual Disabilities - Agustinawati, Sri; Suparno, Suparno (Journal of Innovation and Research in Primary Education, 2025)
Children with mild intellectual disabilities often experience significant delays in fine motor skill development, affecting academic readiness and functional independence. This study investigated the effectiveness of finger painting intervention in improving fine motor skills among children with mild intellectual disabilities aged 5-6 years. Employing Classroom Action Research methodology, two children at State Kindergarten 2, Muara Ancalong District, participated in three intervention cycles conducted from March to June 2025. Fine motor skills were assessed using observational checklists measuring finger coordination, grip strength, hand-eye coordination, and task completion across four performance categories. Data were analyzed descriptively and triangulated through observations, interviews, and documentation. Both participants demonstrated substantial improvement, progressing from a baseline mean score of 26 (Needs Stimulation) to 51 (Independent) following three cycles. Participant AS advanced from 37 to 52, while Participant AD improved from 15 to 50, representing a 96% overall improvement. Systematically implemented finger painting intervention significantly enhances fine motor skills in children with mild intellectual disabilities. The multisensory, play-based approach proved effective when embedded within structured pedagogical frameworks with continuous assessment and individualized adaptations.